On Azumaya Galois extensions and skew group rings - George Szeto (International Journal of Mathematics and Mathematical Sciences)
Two characterizations of an Azumaya Galois extension of a ring are given in terms of the Azumaya skew group ring of the Galois group over the extension and a Galois extension of a ring with a special Galois system is determined by the trace of the Galois group.